2009
DOI: 10.1007/s11062-009-9073-4
|View full text |Cite
|
Sign up to set email alerts
|

Topography of Fos-Immunoreactive and NADPH-d-Reactive Neurons in the Limbic Structures of the Basal Forebrain and in the Hypothalamus during Realization of Motivated Operant Movements in Rats

Abstract: We estimated in rats the expression of early gene c-fos (marker of neuronal activation) and NADPH-diaphorase activity (NO-synthase marker) in the limbic structures of the basal forebrain and in the hypothalamus. Estimations were performed in the norm, in the state of starvation, and after realization of long-lasting (repeated 4 to 12 times per minute for 30 min) motivated stereotyped food-procuring forelimb movements. In food-deprived animals, a significantly greater (Р < 0.05), as compared with the control, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Recently, it was demonstrated that cellular activity (according to the pattern of c-fos expression) in some nuclei, such as LH and Ра, increases considerably in animals subjected to long-lasting food deprivation [9,10]. At the same time, bilateral destruction of these nuclei did not result in the disappearance of food-procuring behavior [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was demonstrated that cellular activity (according to the pattern of c-fos expression) in some nuclei, such as LH and Ра, increases considerably in animals subjected to long-lasting food deprivation [9,10]. At the same time, bilateral destruction of these nuclei did not result in the disappearance of food-procuring behavior [11].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we examined the distribution of Fosimmunoreactive (Fos-ir) and NADPH-d-reactive (NADPH-dr) neurons in different hypothalamic nuclei of rats under conditions of starvation (food deprivation) and after intensification of motor activity directed toward reaching for and capturing of food (unilateral operant food-procuring forelimb movements) [10]. Special attention was focused on the investigation of changes in those hypothalamic nuclei that are involved in the formation of direct or indirect influences on cortical and subcortical structures responsible for the formation of motor commands.…”
Section: Introductionmentioning
confidence: 99%